Oblique Dorsiflexion Osteotomy of the Distal Tibia for Fixed Ankle Equinus: Surgical Technique - Olleac, Ramiro (2024)
Aim: There are significant challenges in the treatment of a severe rigid ankle equinus caused by a flat-topped talus, arthrogryposis, burn sequelae, or extensive scarring. Conventional approaches, such as soft tissue releases, often fail due to joint incongruence or compromised soft tissues, thereby necessitating supramalleolar osteotomies. The classic transverse supramalleolar osteotomy (TSO) of the distal tibia can lead to secondary anterior translation of the centre of rotation of the ankle and alters mechanical and anatomical axes. An alternative technique involves an oblique closing wedge osteotomy of the distal tibia, with a fulcrum near the ankle joint. This technical note delineates the planning parameters and procedural steps for the oblique dorsiflexion osteotomy of the distal tibia (ODODT). Method: Using an anterior approach to the distal tibia, the “alpha angle,” which determines the size of the closing wedge required for the foot to be plantigrade, is resected with a fulcrum at the most posterior part of the ankle joint, ensuring that the posterior cortex remains intact. The inclination of this resected wedge is planned preoperatively and is referred to as the “beta angle.” This aims to equalise the lengths on both sides of the osteotomy. For osteotomy fixation, 2 or 3 cannulated screws in lag mode are employed. Postoperatively, a short cast boot is used for 6 weeks. Results: The ODODT is a salvage solution for severe rigid ankle equinus when first-line foot and ankle procedures are impractical due to tibiotalar incongruence or poor soft tissues. Advantages include minimal translation of the centre of rotation of the ankle, excellent stability when the posterior cortex remains intact, avoidance of large internal fixation devices, and cost-effectiveness, making it suitable for low-resource settings.